Optimising Worldviews for a Flourishing Planet: Exploring the Principle of Right Relationship - Wendy Ellyatt (Challenges)
Worldviews, the foundational assumptions guiding human behaviour and societal systems, are pivotal in shaping planetary health and human flourishing. This paper discusses two divergent worldviews that have prevailed in human populations over time and which are still evident today: the Holistic/Non-linear Worldview, which emphasises interconnectedness and harmony with nature, and the Dualistic/Linear Worldview, which prioritises human-centric activities and the more recent exploitation of nature. The characteristics of human worldviews are explored, including how these are formed in early life via the vital role of human communication and storytelling and the expressive role of the arts. To support the future of human flourishing, this paper makes the case for an integrative worldview that would enable us to embrace paradox and complexity, to seek synthesis, and to promote an integrated approach that reconciles the tensions between seemingly opposing ways of understanding our world. The principle of “Right Relationship”—fostering reciprocal, respectful, and sustainable interactions between humans and the natural world—is examined as a possible framework that could be employed to help humanity navigate today’s global crises and create the conditions for a sustainable, flourishing future.